2009
DOI: 10.1590/s0102-311x2009001100013
|View full text |Cite
|
Sign up to set email alerts
|

Sustentabilidade financeira e econômica do gasto público em saúde no nível municipal: reflexões a partir de dados de municípios mato-grossenses

Abstract: O financiamento do SUS é regido pelo modelo de federalismo fiscal, pelas regras de partilha do Orçamento da Seguridade Social (OSS), por normas do Ministério da Saúde, e pela Emenda Constitucional nº. 29 (EC-29), que vincula à saúde recursos dos entes federados brasileiros. Discute-se aqui a sustentabilidade do gasto público com saúde no nível municipal. Foram estudados 21 municípios, utilizando-se dados dos balanços municipais. De 1996 a 2006 as receitas correntes gerais per capita subiram 280% acima da infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
6
0
7
Order By: Relevance
“…Studies have shown variations between municipalities regarding budget allocation in the health sector, especially given the socioeconomic diversity and the different liability profiles assumed by them regarding service provision, producing inequalities between them 9,11,12 . Data from municipalities of Mato Grosso indicate that the general budget composition of municipalities varies widely according to their size, especially with regard to revenues generated from their own taxation and Union transfers 17 . In a state in northeastern Brazil, it was observed that the funds allocated to primary healthcare have a greater representation in municipal spending, but without homogeneity in its application 13 .…”
mentioning
confidence: 99%
“…Studies have shown variations between municipalities regarding budget allocation in the health sector, especially given the socioeconomic diversity and the different liability profiles assumed by them regarding service provision, producing inequalities between them 9,11,12 . Data from municipalities of Mato Grosso indicate that the general budget composition of municipalities varies widely according to their size, especially with regard to revenues generated from their own taxation and Union transfers 17 . In a state in northeastern Brazil, it was observed that the funds allocated to primary healthcare have a greater representation in municipal spending, but without homogeneity in its application 13 .…”
mentioning
confidence: 99%
“…Several other studies have pointed to the growth of both municipal revenue and municipal health expenditure 14,[17][18][19] .…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Arretche 12 As transferências condicionadas podem induzir à descentralização, pois condicionam os repasses à oferta descentralizada de certos programas 14 , representando um forte estímulo para a adesão municipal 15 . Diante disso, aconteceu aumento da oferta municipal de serviços de atenção básica à saúde?…”
Section: Efeitos Das Transferências Condicionadasunclassified